On Some Extended Results in Functional \(q(t)\)-Calculus: Theoretical and Numerical Applications - Manjarekar, S. S.; Nikam, V. R. (Communications in Mathematics and Applications, 2025)
This paper provides further applications of a functional approach to quantum calculus, towards functional \(q(t)\)-integral, functional \(q(t)\)-Taylor’s formula difference equations with variable coefficients together with functional quantum congruence theory.
Keywords: q- calculus; q - Identities; Hypergeometric functions; Quantum calculus